Gain-of-function mutations in DNMT3A in patients with paraganglioma. (December 2018) - Remacha, Laura; Currás-Freixes, Maria; Torres-Ruiz, Raúl; Schiavi, Francesca; Torres-Pérez, Rafael; Calsina, Bruna; Letón, Rocío; Comino-Méndez, Iñaki; Roldán-Romero, Juan; Montero-Conde, Cristina; Santos, María; Pérez, Lucía; et al.
Abstract Purpose The high percentage of patients carrying germline mutations makes pheochromocytomas/paragangliomas the most heritable of all tumors. However, there are still cases unexplained by mutations in the known genes. We aimed to identify the genetic cause of disease in patients strongly suspected of having hereditary tumors. Methods Whole-exome sequencing was applied to the germlines of a parent–proband trio. Genome-wide methylome analysis, RNA-seq, CRISPR/Cas9 gene editing, and targeted sequencing were also performed. Results We identified a novel de novo germline mutation inDNMT3A, affecting a highly conserved residue located close to the aromatic cage that binds to trimethylated histone H3.DNMT3A -mutated tumors exhibited significant hypermethylation of homeobox-containing genes, suggesting an activating role of the mutation. CRISPR/Cas9-mediated knock-in in HeLa cells led to global changes in methylation, providing evidence of the DNMT3A-altered function. Targeted sequencing revealed subclonal somatic mutations in six additional paragangliomas. Finally, a second germlineDNMT3A mutation, also causing global tumor DNA hypermethylation, was found in a patient with a family history of pheochromocytoma. Conclusion Our findings suggest thatDNMT3A may be a susceptibility gene for paragangliomas and, if confirmed in future studies, would represent the first example of gain-of-function mutations affecting a DNA methyltransferase gene involved in cancer predisposition.